Modelos para estimar a área foliar de abóbora por meio de medidas lineares - SILVA, NATAN FONTOURA DA; FERREIRA, FRANCISCO AFFONSO; FONTES, PAULO CEZAR RESENDE; CARDOSO, ANTONIO AMÉRICO (Revista Ceres, 2015)
.